PENGARUH SALINITAS TERHADAP PENETASAN TELUR IKAN JAMBAL SIAM (Pangasius hypohthalmus) - Beny Heltonika (Universitas Sriwijaya, 2014)
ABSTRACT Salinity have effect on eggs hatching of Cat Fish, Pangasius hypohthalmus. This research was begin from August to October 2005 at the laboratory of hatchery, Faculty of Fisheries and Marine Science, Riau University, this researchs were studied to know effect of salinity on eggs hatching of cat fish, and to know the optimum Salinity on eggs hatching of cat fish in range salinity ( 0 ‰, 2 ‰, 4 ‰ and 6‰). This research used 12 incubation aquaria (614 eggs/aquaria), with capacities 34.22 litre of salinity water. This research used experimental methode and complette random design with 3 time replay. Result of experiment was showing, if salinity have effect on eggs hatching of cat fish, Pangasius hypohthalmus. Eggs of cat fish still can tolerate the salinity until 6 ‰. Eggs incubated at 4 ‰ salinity showed the best hatching rate (89.10). The qualiy of water during the researched about 28-31 OC in hatching temperature, 26-29 OC in survival rate, pH 6.58-7.60 and Dissolve Oxigen 6.3-7.4 ppm. Range of salinity in every treatment, for salinity 0 (0-0.2 ppt), salinity 2 (1.8-2.0 ppt), salinity 4 ( 3.6-4.0 ppt) and salinity 6 (5.7-6.0 ppt). Keywords: Eggs, Pangasius hypohthalmus, Salinity